BIDUAN DANGDUT DI DESA PAGAR MAYANG KECAMATAN TAMBUSAI UTARA KABUPATEN ROKAN HULU - Utami, Diah Rizki; Asriwandari, Hesti (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
Dangdut singer is part of the dangdut music industry which has become a means of public entertainment, having a number of fans who like it. But on the one hand, there are presumptions of lenjeh, sexy, sensual and cheap inherent in everyday life. Dangdut singers get stereotypes that tend to be negative both in the family environment and in their neighborhood, so that the formation of self-concept in interpersonal communication with dangdut singers occurs. This description shows that dangdut singers experience communication barriers that have an impact on harmony in the family, and are always followed by feelings of inferiority and tend to be less confident in living a social life. For this reason the writer wants to know how their background becomes a singer. And how the self-concept of singer to his activities as a singer dangdut. The method used is descriptive qualitative method. From the results of the study it can be concluded that the background of the informants being a choir is one of them is the economic factor, wanting to increase income or investment to comply with lifestyle. For the stage of becoming a singer there are also a number of processes that they must go through, starting from experiencing rejection from the family because they choose work that is considered to have a negative label, and Until they have to deal with problems that come from those closest to them, because they do not support their work to cause divorce. In undergoing work as a singer the description of self-concept can originate from interactions between oneself and with others (their social environment). therefore, researchers use self-concept theory as a way of looking at oneself about oneself to understand one's own existence and to understand others. Keywords: Dangdut singer, self concept